Acetylation Rather than H50Q Mutation Impacts the Kinetics of Cu(II) Binding to α‐Synuclein. Issue 23 (15th November 2021) - Teng, Xiangyu; Sheveleva, Alena; Tuna, Floriana; Willison, Keith R.; Ying, Liming
Abstract: The front cover artwork is provided by the group of Liming Ying at Imperial College London. The image shows that N‐terminal acetylation of α‐synuclein shifts the binding from the N‐terminus to His50 and significantly slows down the binding reaction. Read the full text of the Article at 10.1002/cphc.202100651 . Abstract : "His50 in αSyn is not involved in high‐affinity Cu 2+ binding, whereas N‐terminal acetylation strongly reduces the Cu 2+ binding affinity of αSyn. The αSyn‐Cu(II) complex can be readily reduced under physiological conditions by glutathione (GSH) instead of ascorbate…" This and more about the story behind the front cover can be found in the Article at 10.1002/cphc.202100651 .